Self-Calibrated Measurement of Frequency Response for Broadband Photodetectors Based on Two-Tone Photonic Sampling - Wang, Mengke; Xu, Ying; He, Yutong; Liu, Zhao; Zhang, Yali; Zhang, Zhiyao; Li, Heping; Zhang, Shangjian; Liu, Yong (Frontiers in Physics, 2021)
A self-calibrated method to measuring the frequency responses of broadband photodetectors (PDs) is proposed based on photonic pulse sampling of two-tone microwave signal, with the help of a mode-locked laser diode (MLLD) and a Mach-Zehnder modulator (MZM). Firstly, the repetition frequency of the optical comb from the MLLD divides the whole measuring frequency range into several segments. Then, a close-spaced two-tone signal modulates every comb tooth through the MZM and generates the sum- and difference-frequency products, working as the probing signal to extract the frequency response of the PD in every segment. Hyper-fine frequency response of the PD at any frequency point can be obtained in every segment by subtly varying the center frequency of the two-tone signal while keeping the difference frequency fixed. Finally, the whole frequency response of the PD in ultra-wide frequency range is obtained by seamlessly stitching the segmental frequency responses. In our experiment, measurement of a commercial PD is demonstrated up to 49.765 GHz with an optical comb at the repetition frequency of 9.953 GHz and a two-tone modulation up to 4.9765 GHz. The measured results are compared with those by using the traditional methods to check accuracy. Moreover, the uneven responses of the MLLD and the MZM are fully subtracted, verifying the ultra-wideband, hyperfine and self-calibrated measurement of PDs based on the two-tone photonic sampling.